A Trickle-Down Theory of Incentives with Applications to Privatization and Outsourcing - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2004)
The make-or-buy decision is analyzed in a three-layer principal-management-agent model. There is a cost-saving/quality tradeoff in effort provision. The principal faces the choice between employing an in-house management and contracting with an independent management; the cost-saving incentives facing the management are weaker in the former case. Cost-saving incentives trickle-down to the agent, affecting the cost-saving/quality tradeoff. It is shown that: weak cost-saving incentives to the management promotes quality if it is hard enough to meaurse; a more severe quality-control problem between the principal and the management, as well as a higher valuation of quality, makes an in-house management more attractive.
Keywords: D23; L22; L24; 330; make-or-buy decision; multitask principal-agent problem; contracting out